Triglyceride‐cholesterol imbalance across lipoprotein subclasses predicts diabetic kidney disease and mortality in type 1 diabetes: the FinnDiane Study - Mäkinen, V.‐P.; Soininen, P.; Kangas, A. J.; Forsblom, C.; Tolonen, N.; Thorn, L. M.; Viikari, J.; Raitakari, O. T.; Savolainen, M.; Groop, P.‐H.; Ala‐Korpela, M. (Journal of internal medicine, 2013)
Background Circulating cholesterol (C) and triglyceride (TG) levels are associated with vascular injury in type 1 diabetes (T1DM). Lipoproteins are responsible for transporting lipids, and alterations in their subclass distributions may partly explain the increased mortality in individuals with T1DM. Design and subjects A cohort of 3544 individuals with T1DM was recruited by the nationwide multicentre FinnDiane Study Group. At baseline, six very low‐density lipoprotein VLDL, one intermediate‐density lipoprotein IDL, three low‐density lipoprotein LDL and four higher high‐density lipoprotein HDL subclasses were quantified by proton nuclear magnetic resonance spectroscopy. At follow‐up, the baseline data were analysed for incident micro‐ or macroalbuminuria (117 cases in 5.3 years), progression from microalbuminuria (63 cases in 6.1 years), progression from macroalbuminuria (109 cases in 5.9 years) and mortality (385 deaths in 9.4 years). Univariate associations were tested by age‐matched cases and controls and multivariate lipoprotein profiles were analysed using the self‐organizing map (SOM). Results TG and C levels in large VLDL were associated with incident albuminuria, TG and C in medium VLDL were associated with progression from microalbuminuria, and TG and C in all VLDL subclasses were associated with mortality. Large HDL‐C was inversely associated with mortality. Three extreme phenotypes emerged from SOM analysis: (i) low C (<3% mortality), (ii) low TG/C ratio (6% mortality), and (iii) high TG/C ratio (40% mortality) in all subclasses. Conclusions TG–C imbalance is a general lipoprotein characteristic in individuals with T1DM and high vascular disease risk.